DEVELOPMENT OF DIGITAL ECONOMY IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
This article presents the concept of digital economy, definitions of digital economy, development of digital economy, number of internet users, implementation of digital economy program, main indicators and criteria of digital economy.